2015
DOI: 10.14203/mri.v36i2.38
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance of Potentially Toxic Epiphytic Dinoflagellates and Nutrients From Bali and Gili Trawangan, Indonesia

Abstract: There are strong indicators that the degradation of coral reefs may increase the intensity and frequency of ciguatera fish poisoning (CFP) outbreaks when denuded reef surfaces are colonised by macro algae that are the preferred hosts of toxic dinoflagellates that can cause the disease. Ciguatera field studies have concentrated on the dinoflagellate genus Gambierdiscus, well known to be the producer of ciguatoxin precursors. Moreover the potential of toxins from other dinoflagellate genera such as Prorocentrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Four of those sites showed a direct correlation with the Prorocentrum abundance and the water column DIN. A similar study of a smaller lagoon in Nusa Dua, Bali, Indonesia also found a significant correlation between the dinoflagellate genera Prorocentrum with the DIN in the water column (Skinner et al, 2012), and a benthic Prorocentrum gillespii bloom in the sediment of Muri lagoon, Rarotonga was also correlated with nutrients (Skinner et al, 2009), where critical levels for nutrient thresholds were also exceeded at both sites. The genus Prorocentrum is known to be involved in ciguatera (Rongo and Van Woesik, 2010), so nutrient thresholds set for coral reefs should be employed, as these levels once exceeded, can assist to create HABs.…”
Section: Discussionmentioning
confidence: 79%
“…Four of those sites showed a direct correlation with the Prorocentrum abundance and the water column DIN. A similar study of a smaller lagoon in Nusa Dua, Bali, Indonesia also found a significant correlation between the dinoflagellate genera Prorocentrum with the DIN in the water column (Skinner et al, 2012), and a benthic Prorocentrum gillespii bloom in the sediment of Muri lagoon, Rarotonga was also correlated with nutrients (Skinner et al, 2009), where critical levels for nutrient thresholds were also exceeded at both sites. The genus Prorocentrum is known to be involved in ciguatera (Rongo and Van Woesik, 2010), so nutrient thresholds set for coral reefs should be employed, as these levels once exceeded, can assist to create HABs.…”
Section: Discussionmentioning
confidence: 79%
“…Some of the acute diseases caused by toxins from microalgae in the HABs group are paralytic shellfish poisoning (PSP), amnesic shellfish poisoning (ASP), diarrhetic shellfish poisoning (DSP) (Fukuyo et al 2011;Krock et al 2018), and ciguatera fish poisoning (CFP) (Skinner et al 2011). These toxins are hazardous to human health because they attack the nervous system and interfere with respiration and digestion.…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are related to the human consumption of fish and shellfish. Many types of toxic phytoplankton can be found in Indonesian coastal waters, including several Dinoflagellate species from the genera Noctiluca, Gymnodinium, Cochlodinium, Ceratium, Peridinium, Gonyaulax, Ostreopsis, Prorocentrum, and Gambierdiscus (Adnan 1984;Adnan 1989;Skinner et al 2011;Hasani et al 2013;Aditya et al 2015). One HAB event in 1993 took place in Jakarta Bay, where a mass fishkill was caused by the excessive abundance of phytoplankton that can cause HABs.…”
Section: Introductionmentioning
confidence: 99%
“…Prorocentrum has been reported in Indonesian waters. For instance, in Seribu Islands (Penjaliran Barat Island, Pramuka Island, Panggang Island, Semak Daun Island, Pari Island, Air Island and Tidung Island) (Widiarti 2002;Widiarti 2011;, Belitung Island (Buyut Island, Kelayang Cape, and Keran Island) (Widiarti 2010), Bali waters (Kuta, Sanur, and Nusa Dua), Lombok (Gili Trawangan) (Skinner et al 2011), west coast of South Sumatera and Bintan Island coast-Riau Islands (Thamrin 2014), Padang city beach waters (Dwivayana 2015;Eboni et al 2015;Oktavian et al 2017;Seygita et al 2015), North Lombok (Gili Meno and Gili Air) (Widiarti et al 2016a), South Lampung waters (Pahawang Besar Island and Kelagian Kecil Island) (Widiarti and Adi 2016), and Weh Island waters-North Aceh (Rubiah Island) (Widiarti et al 2016b). However, no detailed observation on cell surface morphology has been recorded.…”
Section: Introductionmentioning
confidence: 99%